A comparison between risk-factor guidance for neonatal early-onset sepsis and Kaiser Permanente sepsis risk calculator in a Greek cohort. (April 2021) - Rallis, Dimitrios; Balomenou, Foteini; Karantanou, Konstantina; Kappatou, Kleio; Tzoufi, Meropi; Giapros, Vasileios
Abstract: Background: The management of neonates with early-onset sepsis (EOS) is based on maternal risk factors and infant clinical indications. An online sepsis risk calculator (SRC) has been established taking into consideration how clinical appearance modifies the initial risk for EOS. Aims: To compare our clinical practice based on risk-factor guidance with that projected through the application of the SRC. Study design: Retrospective cohort study. Methods: All neonates ≥34 weeks' gestation, during 01/2019–8/2020. The SRC was applied retrospectively to determine the recommendation. EOS was defined based on a positive blood or cerebrospinal fluid culture-proven infection within 72 h of age. Clinical sepsis was defined according to the European Medicine Agency criteria. Outcome measures: Differences on antibiotic administration and management. Results: Overall, 2084 infants were identified, of whom 150 (7%) received antibiotics. Of them, 34 infants were diagnosed with clinical sepsis, while one was diagnosed with culture positive-proven EOS. Applying SRC, 87 (4%) infants would have received antibiotics. Clinical sepsis was diagnosed in 29 infants, while one infant had culture positive-proven EOS. Sixty-seven of 150 (45%) infants that received antibiotics would not have been treated based on SRC; five infants that developed clinical sepsis would have been missed with SRC. A 99.7% agreement between both guidance was found regarding infants not indicated for antibiotics. SRC application led to an absolute reduction of antibiotic administration by 2.93% (95% CI 2.19–3.75), p  < 0.0001. Conclusions: The adoption of SRC would have significantly reduced antibiotic usage; however, a significant portion of cases with clinical EOS would have been missed. Highlights: Neonatal early-onset sepsis management is based on maternal and infant risk factors. A sepsis risk calculator had been developed online deriving recommendation. Sepsis risk calculator application led to reducing antibiotics by 2.93%. Sepsis calculator would have missed a significant portion of clinical sepsis cases.